Потенціал фізичного виховання щодо формування компетенцій у студентів технічних вузів - Борейко, Наталя Юріївна; Азаренкова, Любов Леонідівна (Національний педагогічний університет ім. М. П. Драгоманова, 2019)
Встановлено, що у сучасний період фізична культура має великий потенціал для формування різних компетенцій. Під час цих занять з фізичного виховання студенти повинні отримувати:1) знання про фізичну культуру та фізичну підготовку: 2) навички збереження здоров’я, підвищення працездатності: 3) ціннісні орієнтації на самовдосконалення: 4) морально-вольові та лідерські якості; 5) досвід фізкультурної і спортивної діяльності, спілкування; 6) прийоми самореалізації. Для формування ключових компетенції (загальнокультурної, навчально-пізнавальної, комунікативної, соціальної, особистісної, здоров’язберігаючої, лідерської) необхідно проводити лекції, бесіди, практичні та методичні заняття, а також допомагати в організації самостійних занять. Для успішного впровадження компетентнісного підходу в НТУ «ХПІ»: необхідно дотримуватись певних етапів їх формування, а саме: 1) мотиваційного; 2) етичного; 3) когнітивного; 4) поведінкового; 5) соціального.

The purpose of the research is to determine the potential of physical education for the formation of different competencies among students of higher technical education institutions. The study clarifies the concept of "competence" and identified which key competences are needed for graduates of higher technical education institutions. The level of formation of different competencies is determined at students who are engaged in different sections. The system of physical education for students of higher technical educational institutions is considered through the implementation of the competence approach. It is established that in the modern period physical culture has great potential for forming different competencies. Classes in a higher technical educational institution with different types of motor activity and sports allow creating conditions for selfimprovement and not only physical but also spiritual, social, personal and mental. During these physical education classes, students must receive: 1) knowledge of physical culture and physical training: 2) skills of preserving health, improving work capacity: 3) value orientations for self-improvement: 4) moral and volitional and leadership qualities; 5) experience of physical culture and sports activities, communication; 6) techniques of self-realization. To form the key competencies (general cultural, educational, cognitive, communicative, social, personal, health preserving, leadership) it is necessary to conduct lectures, conversations and practical, methodological classes and help in the organization of independent classes.For successful implementation of the competence approach in NTU "KhPI": certain stages of their formation must be observed, namely; 1) motivational; 2) ethical; 3) cognitive; 4) behavioral; 5) social.
Potential of physical education in the formation of competencies among students of technical universities
Keywords: компетентнісний підхід; фізичне виховання; компетенції; студенти; тести; competence approach; physical education; competence; students; tests